Math, asked by shalvi76, 8 months ago

prove that cos A / ( 1- tan A) + sin²A /( sin A - cos A ) = sin A + cos A ​

Answers

Answered by MaIeficent
11

Step-by-step explanation:

To Prove:-

 \rm \dfrac{cosA}{1 - tanA}  +  \dfrac{ {sin}^{2}A}{sinA - cosA}  =  sinA +cosA

Proof:-

 \rm LHS =  \dfrac{cosA}{1 - tanA}  +  \dfrac{ {sin}^{2}A}{sinA - cosA}

 \rm  =  \dfrac{cosA}{1 - \dfrac{sinA}{cosA}  }  +  \dfrac{ {sin}^{2}A}{sinA - cosA} \: \: \: \: \: \: \:\:\: \bigg(\because tanA = \dfrac{sinA}{cosA}\bigg)

 \rm  =  \dfrac{cosA}{ \dfrac{cosA - </p><p>sinA}{cosA}  }  +  \dfrac{ {sin}^{2}A}{sinA - cosA}

 \rm  =  \dfrac{cosA \times cosA }{ {cosA - </p><p>sinA}  }  +  \dfrac{ {sin}^{2}A}{sinA - cosA}

 \rm  =  \dfrac{cos^{2} A }{ {cosA - </p><p>sinA}  }  +  \dfrac{ {sin}^{2}A}{sinA - cosA}

 \rm  =  \dfrac{cos^{2} A }{ {cosA - </p><p>sinA}  }  +   \bigg(\dfrac{ { - (sin}^{2}A)}{ - (sinA - cosA)} \bigg)

 \rm  =  \dfrac{cos^{2} A }{ {cosA - </p><p>sinA}  }  +   \bigg(\dfrac{ { - (sin}^{2}A)}{  cosA - sinA} \bigg)

 \rm  =  \dfrac{cos^{2} A }{ {cosA - </p><p>sinA}  }   - \dfrac{ { sin}^{2}A}{  cosA - sinA}

 \rm  =  \dfrac{cos^{2} A  -  {sin}^{2} A}{ {cosA - </p><p>sinA}  }

 \rm  =  \dfrac{(cosA   + sin A)(cosA    -  sin A)}{ {(cosA - </p><p>sinA)}  }

 \rm  =  cosA   + sin A

= RHS

LHS = RHS

Hence Proved

Answered by BrainlyAryabhatta
1

Answer:

Step-by-step explanation:

To Prove:-

\rm \dfrac{cosA}{1 - tanA} + \dfrac{ {sin}^{2}A}{sinA - cosA} = sinA +cosA

1−tanA

cosA

+

sinA−cosA

sin

2

A

=sinA+cosA

Proof:-

\rm LHS = \dfrac{cosA}{1 - tanA} + \dfrac{ {sin}^{2}A}{sinA - cosA}LHS=

1−tanA

cosA

+

sinA−cosA

sin

2

A

\rm = \dfrac{cosA}{1 - \dfrac{sinA}{cosA} } + \dfrac{ {sin}^{2}A}{sinA - cosA} \: \: \: \: \: \: \:\:\: \bigg(\because tanA = \dfrac{sinA}{cosA}\bigg)=

1−

cosA

sinA

cosA

+

sinA−cosA

sin

2

A

(∵tanA=

cosA

sinA

)

\rm = \dfrac{cosA}{ \dfrac{cosA - < /p > < p > sinA}{cosA} } + \dfrac{ {sin}^{2}A}{sinA - cosA}=

cosA

cosA−</p><p>sinA

cosA

+

sinA−cosA

sin

2

A

\rm = \dfrac{cosA \times cosA }{ {cosA - < /p > < p > sinA} } + \dfrac{ {sin}^{2}A}{sinA - cosA}=

cosA−</p><p>sinA

cosA×cosA

+

sinA−cosA

sin

2

A

\rm = \dfrac{cos^{2} A }{ {cosA - < /p > < p > sinA} } + \dfrac{ {sin}^{2}A}{sinA - cosA}=

cosA−</p><p>sinA

cos

2

A

+

sinA−cosA

sin

2

A

\rm = \dfrac{cos^{2} A }{ {cosA - < /p > < p > sinA} } + \bigg(\dfrac{ { - (sin}^{2}A)}{ - (sinA - cosA)} \bigg)=

cosA−</p><p>sinA

cos

2

A

+(

−(sinA−cosA)

−(sin

2

A)

)

\rm = \dfrac{cos^{2} A }{ {cosA - < /p > < p > sinA} } + \bigg(\dfrac{ { - (sin}^{2}A)}{ cosA - sinA} \bigg)=

cosA−</p><p>sinA

cos

2

A

+(

cosA−sinA

−(sin

2

A)

)

\rm = \dfrac{cos^{2} A }{ {cosA - < /p > < p > sinA} } - \dfrac{ { sin}^{2}A}{ cosA - sinA}=

cosA−</p><p>sinA

cos

2

A

cosA−sinA

sin

2

A

\rm = \dfrac{cos^{2} A - {sin}^{2} A}{ {cosA - < /p > < p > sinA} }=

cosA−</p><p>sinA

cos

2

A−sin

2

A

\rm = \dfrac{(cosA + sin A)(cosA - sin A)}{ {(cosA - < /p > < p > sinA)} }=

(cosA−</p><p>sinA)

(cosA+sinA)(cosA−sinA)

\rm = cosA + sin A=cosA+sinA

= RHS

LHS = RHS

Hence Proved

Similar questions